HUBUNGAN ANEMIA PADA IBU HAMIL TERHADAP KEJADIAN BERAT BADAN LAHIR RENDAH DI 2 RUMAH SAKIT SWASTA KOTA LHOKSEUMAWE TAHUN 2020 - Muhammad Iqbal Maulana; Mauliza Mauliza; Mardiati Mardiati; Noviana Zara; Teuku Yudhi Iqbal (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2022)
Low birth weight (LBW) is a infant whose weight is less than 2500 grams. Internationally, LBW is still seen as a health problem that is quite prominent because it has a high enough risk to experience death in the neonatal period, which is 40 times greater than babies born with normal weight. Data from the WHO in 2018, the prevalence of babies with LBW in the world is 15.5% or about 20 million babies born every year, of which about 96.5% of them occur in developing countries. Based on the results of Riskesdas in 2018, one of the most common causes of infant mortality in Indonesia is LBW, which is 34%. The birth rate of babies with LBW in Indonesia reaches 350,000 every year where the prevalence of LBW in Indonesia is 6.2%. One of the causes of LBW is the poor nutritional status of the mother, one of which is anemia. The purpose of this study was to determine the relationship between anemia in pregnant women and the incidence of low birth weight (LBW) in 2 private hospitals in Lhokseumawe. This research is an analytic observational study with a cross sectional study approach. The sampling technique used is total sampling with a total of 154 respondents. The data used is secondary data derived from medical records. Data analysis was performed using Chi-square’s test. The results showed is no relationship between maternal anemia and the incidence of LBW.